Flipbook Poetry Goa Terawang Based on Cooperative Script: Development, Validation, and Effectiveness in Poetry Reading Skills - Syifa, Aulia Hasna Nur; Purwati, Panca Dewi (JOLLT Journal of Languages and Language Teaching, 2026)
The ability to read poetry is an essential competency in literary literacy in elementary schools, but students' mastery of intonation, articulation, and interpretation of meaning is often hampered by the limitations of interactive and contextual learning media. Although previous literature has partially explored the use of digital media and cooperative learning models, the integration of poetry based on local wisdom, audio models, and collaborative interactions in a single platform is still very limited. This study aims to develop the Goa Terawang Poetry Flipbook based on the Cooperative Script Model and to test its validity and effectiveness in improving the poetry reading skills of fourth-grade students at SDN Kediren, Blora. This research is a Research and Development (R&D) study adapted from Sugiyono's model through eight stages: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product testing, (7) product revision, and (8) field testing. The developed media integrates poetry texts containing local songs, visual illustrations, and expressive audio models accessed through QR codes, combined with a cooperative script model that includes paired activities so that children can practice more confidently with their peers. Expert validation results showed a very high level of feasibility, namely 92.8% for the material aspect and 94.6% for the media aspect. Effectiveness tests showed a significant increase in students' poetry reading skills, as evidenced by the results of the Paired Sample t-test (P < 0.05) in the product test and the Wilcoxon Signed-Rank test (P < 0.05) in the usage test. The improvement in learning outcomes was categorized as moderate, with N-Gain scores of 61.3% and 60.16%, respectively. In conclusion, the Goa Terawang Poetry Flipbook is declared valid and effective as an alternative learning medium to improve elementary school students' poetry reading skills.